2018
DOI: 10.1126/scisignal.aan5785
|View full text |Cite
|
Sign up to set email alerts
|

The unfolded protein response regulator ATF6 promotes mesodermal differentiation

Abstract: ATF6 encodes a transcription factor that is anchored in the endoplasmic reticulum (ER) and activated during the unfolded protein response (UPR) to protect cells from ER stress. Deletion of the isoform activating transcription factor 6α (ATF6α) and its paralog ATF6β results in embryonic lethality and notochord dysgenesis in nonhuman vertebrates, and loss-of-function mutations in ATF6α are associated with malformed neuroretina and congenital vision loss in humans. These phenotypes implicate an essential role for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 68 publications
3
56
0
Order By: Relevance
“…In humans, the two ATF6 genes are referred to as ATF6 (also known as ATF6α) and ATF6B (Haze et al, 2001). It has been recently found that hyper-activation of ATF6 in human embryonic stem cells (hESCs) not only promotes their expansion of the ER network, but also biases their differentiation into the mesodermal lineage (Kroeger et al, 2018). Conversely, loss-of-function mutations of ATF6 in induced pluripotent stem cells impede this mesodermal fate specification (Kroeger et al, 2018).…”
Section: The Role Of Atf6 In Animal Developmentmentioning
confidence: 99%
“…In humans, the two ATF6 genes are referred to as ATF6 (also known as ATF6α) and ATF6B (Haze et al, 2001). It has been recently found that hyper-activation of ATF6 in human embryonic stem cells (hESCs) not only promotes their expansion of the ER network, but also biases their differentiation into the mesodermal lineage (Kroeger et al, 2018). Conversely, loss-of-function mutations of ATF6 in induced pluripotent stem cells impede this mesodermal fate specification (Kroeger et al, 2018).…”
Section: The Role Of Atf6 In Animal Developmentmentioning
confidence: 99%
“…Recently, a new role for ATF6a signaling in early stem cell differentiation was identified [113]. It was shown that the activation of ATF6a during stem cell differentiation resulted in the acceleration of differentiation events toward the mesodermal lineage generating functional endothelial cells that were able to undergo in vitro angiogenesis to form blood vessels; ATF6a additionally stimulated the loss of pluripotency [113]. In the same study, ATF6a was found to support the growth and maturation of the ER without activating a comprehensive ER stress responds.…”
Section: Discussionmentioning
confidence: 99%
“…ERS (Kroeger et al, 2018) GSE106847 RNA-seq ATF6 encodes a transcription factor that is activated during the Unfolded Protein Response to protect cells from ER stress. Comparison was made between ATF6-activated and control cells.…”
Section: Datasets Name (Acronym) Access To Data Technologymentioning
confidence: 99%